Survey of cryptic unstable transcripts in yeast. (December 2016) - Vera, Jessica; Dowell, Robin
Abstract Background Cryptic unstable transcripts (CUTs) are a largely unexplored class of nuclear exosome degraded, non-coding RNAs in budding yeast. It is highly debated whether CUT transcription has a functional role in the cell or whether CUTs represent noise in the yeast transcriptome. We sought to ascertain the extent of conserved CUT expression across a variety ofSaccharomyces yeast strains to further understand and characterize the nature of CUT expression. Results We sequenced the WT andrrp6 Δ transcriptomes of threeS.cerevisiae strains: S288c, Σ1278b, JAY291 and theS.paradoxus strain N17 and utilized a hidden Markov model to annotate CUTs in these four strains. Utilizing a four-way genomic alignment we identified a large population of CUTs with conserved syntenic expression across all four strains. By identifying configurations of gene-CUT pairs, where CUT expression originates from the gene 5' or 3′ nucleosome free region, we observed distinct gene expression trends specific to these configurations which were most prevalent in the presence of conserved CUT expression. Divergent pairs correlate with higher expression of genes, and convergent pairs correlate with reduced gene expression. Conclusions Our RNA-seq based method has greatly expanded upon previous CUT annotations inS.cerevisiae underscoring the extensive and pervasive nature of unstable transcription. Furthermore we provide the first assessment of conserved CUT expression in yeast and globally demonstrate possible modes of CUT-based regulation of gene expression.